Membongkar Patriarkhisme Islam sebagai Kearifan Budaya Lokal: Sebuah Kritik Terhadap UU. No. 1 Tahun 1974 Tentang Perkawinan - Habib Shulton Asnawi (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
Patriarchism’s Islam is not a form of accusation that Islam is a patriarchal  religion. Patriarchism’s Islam here is a way of interpretation by certain circles, because of its cultural, political, social and historical role of specific, resulting in the claim that Islam is a religion that favor the ideology of patriarchy. This patriarchal ideology that considers women as inferior beings position than men. This forms a negative paradigm to the framers of the law in particular is the law. No. 1 Year 1974 About Marriage. As a result of the UUP, women in Indonesia, suffered discrimination and injustice, this is certainly a violation of human rights. The protection of women's rights is the duty of the government of Indonesia. Therefore, reform/amendment UUP is a necessity that should be done, in order of justice, equality and protection of human rights, especially as indigenous efforts in Indonesia.